Automated detection of the choroid boundary within OCT image data using quadratic measure filters. - Wagner, M.; Scheibe, P.; Francke, M.; Zimmerling, B.; Frey, K.; Vogel, M.; Luckhaus, S.; Wiedemann, P.; Kiess, W.; Rauscher, F. G. (J Biomed Opt, 2017)
A novel method for the automated detection of the outer choroid boundary within spectral-domain optical coherence tomography image data, based on an image model within the space of functions of bounded variation and the application of quadratic measure filters, is presented. The same method is used for the segmentation of retinal layer boundaries and proves to be suitable even for data generated without special imaging modes and moderate line averaging. Based on the segmentations, an automated determination of the central fovea region and choroidal thickness measurements for this and two adjacent 1-mm regions are provided. The quality of the method is assessed by comparison with manual delineations performed by five trained graders. The study is based on data from 50 children of the ages 8 to 13 that were obtained in the framework of the LIFE Child study at Leipzig University.
Keywords: Adolescent; Child; Choroid/diagnostic imaging; Eye/*diagnostic imaging; Fovea Centralis/diagnostic imaging; Humans; Retina/diagnostic imaging; *Tomography, Optical Coherence